Antimicrobial effects of different concentrations of simvastatin versus triple antibiotic paste on Enterococcus faecalis biofilms at different stages of development - Saeed Rahimi; Negin Ghasemi; Paria Davoudi; Isun Taleb; Mehran Farajollahi; Naghmeh Rahimi Darehchi; Ezatolah Kazeminejad (Tabriz University of Medical Sciences, 2022)
Background. This study assessed the antimicrobial effects of different concentrations of simvastatin versus triple antibiotic paste (TAP) on Enterococcus faecalis biofilms at different stages of development. Methods. In this in vitro study, 70 human single-rooted mature premolars were decoronated, instrumented, and autoclave-sterilized. Next, an E. faecalis suspension was prepared and inoculated into the canals to obtain 4- and 6-week biofilms. After ensuring biofilm formation, the samples in each group were randomly assigned to 5 subgroups (n=12): 1 mg/mL TAP, 10 mg/ mL TAP, 1 mg/mL simvastatin, 10 mg/mL simvastatin, and positive control (phosphate-buffered saline solution). The medicaments were applied in the canals, and the teeth were incubated for one week. Dentin samples were collected by a rotary file, cultured, and the number of E. faecalis colonies was counted. The Kruskal-Wallis, Mann-Whitney U, and Wilcoxon tests were used for data analysis (α=0.05). Results. There were significant differences in colony counts between the two concentrations of TAP and the control group against both 4- and 6-week biofilms (P<0.05). The antibacterial effect of 10 mg/mL TAP and simvastatin was stronger than that of 1 mg/mL concentration against the 4- and 6-week E. faecalis biofilms (P<0.05). Furthermore, 10 mg/mL TAP and simvastatin were more effective against the 4-week biofilms than the 6-week biofilms (P<0.05). Conclusion. According to the present results and since biofilms may remain viable in the root canal system for weeks to months, applying 10 mg/mL TAP and simvastatin might be more effective.